2009
DOI: 10.1111/igc.0b013e3181a8446a
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Lymphedema and Vulval Cancer: Feasibility of Prophylactic Compression Garments and Validation of Leg Volume Measurement

Abstract: The prophylactic use of stockings in this population is feasible, and further larger studies are justified to investigate its role in reducing the incidence of leg lymphedema. The design of these studies should take into account the observer-related variability in measuring leg volume or consider alternative methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 42 publications
0
31
2
Order By: Relevance
“…Changes in leg volume can only be reliably detected when the difference in a significant amount of fluid has been collected in the limb. 20 In addition, multiple methods in the assessment of lymphedema have been developed. In this study, we used the method that is recommended by the International Society of Lymphology.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in leg volume can only be reliably detected when the difference in a significant amount of fluid has been collected in the limb. 20 In addition, multiple methods in the assessment of lymphedema have been developed. In this study, we used the method that is recommended by the International Society of Lymphology.…”
Section: Discussionmentioning
confidence: 99%
“…Complete decongestive therapy Carmeli & Bartoletti, 2011;Dayes et al, 2013;de Godoy & Godoy, 2013;Haghighat et al, 2010;Hwang, Jeong, et al, 2013;Liao et al, 2013;Randheer et al, 2011;Vignes et al, 2013Beck et al, 2012Lasinski et al, 2012;Leal et al, 2009;Ridner, Fu, et al, 2012;Rodrick et al, 2014 Compression bandaging Compression bandaging and compression garments Damstra & Partsch, 2009;Kasseroller & Brenner, 2010;King et al, 2012;Sawan et al, 2009 McNeely et al, 2011…”
Section: Complete Decongestive Therapymentioning
confidence: 99%
“…The time, effort, and dexterity required for bandaging can become burdensome and is not practical or possible for some patients, necessitating the use of an alternative compression method, such as compression garments. Four RCTs were identified that evaluated the comparative effectiveness of compression bandaging and compression garments; arm volume reduction with different bandage pressures; and comparison of low-stretch compression dressings and alginate semirigid bandages (Damstra & Partsch, 2009;Kasseroller & Brenner, 2010;King, Deveaux, White, & Rayson, 2012;Sawan, Mugnai, Lopes Ade, Hughes, & Edmondson, 2009). One systematic review was identified (McNeely, Peddle, Yurick, Dayes, & Mackey, 2011).…”
Section: Likely To Be Effectivementioning
confidence: 99%
See 1 more Smart Citation
“…7 These patient-centered outcome measures should allow for more meaningful assessment of the impact of this condition and treatment outcomes. 6,8,9 Estimates of CL after treatment for vulvar cancer vary by the method of diagnosis and reporting, but range from 9% to 67%. 2,5,10Y15 Inguinal lymph node dissection and RT to the inguinal nodal bed are both individually well-established risk factors for the development of CL in vulvar cancer patients.…”
mentioning
confidence: 99%